2015
DOI: 10.1073/pnas.1501989112
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals transmembrane targets on transplantable midbrain dopamine progenitors

Abstract: An important challenge for the continued development of cell therapy for Parkinson's disease (PD) is the establishment of procedures that better standardize cell preparations for use in transplantation. Although cell sorting has been an anticipated strategy, its application has been limited by lack of knowledge regarding transmembrane proteins that can be used to target and isolate progenitors for midbrain dopamine (mDA) neurons. We used a "FACS-array" approach to identify 18 genes for transmembrane proteins w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
63
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 48 publications
9
63
0
Order By: Relevance
“…As a control, we implanted 250,000 mDA neurons that were generated on 2D Matrigel-coated surfaces as previously reported1. Six weeks post-implantation, a time point at which previous mDA neuron transplantation studies begin to report functional improvements in PD rat models36, we sacrificed the animals and investigated graft survival (Figs 4 and S8). TH and FOXA2 expression was observed in the HNA+ surviving cells among both the 3D (4a–j) and 2D (4k–n) generated mDA neuron groups.…”
Section: Resultsmentioning
confidence: 99%
“…As a control, we implanted 250,000 mDA neurons that were generated on 2D Matrigel-coated surfaces as previously reported1. Six weeks post-implantation, a time point at which previous mDA neuron transplantation studies begin to report functional improvements in PD rat models36, we sacrificed the animals and investigated graft survival (Figs 4 and S8). TH and FOXA2 expression was observed in the HNA+ surviving cells among both the 3D (4a–j) and 2D (4k–n) generated mDA neuron groups.…”
Section: Resultsmentioning
confidence: 99%
“…These authors also identified the selectable surface marker Alcam (26). In a report published in PNAS, Bye et al (27) demonstrate another strategy that also obtained evidence of at least one of these markers (Alcam). Bye et al base their analysis on mRNA expression from sorted neurogenin2-GFP progenitor cells (28) and then comparatively by using the GFP − fraction (nondopaminergic) cell populations expressing Lmx A1 GFP (11), and by post hoc analysis subtracted less-relevant mRNA expression.…”
Section: Cell Sorting For Parkinson's Disease Studiesmentioning
confidence: 96%
“…This arithmetic provided support for a separate analysis and selection of transmembrane proteins expressed only on developing midbrain dopamine neurons. Bye et al (27) prioritized four surface transmembrane receptor marker candidates: Alcam, Chl1, Gfra1, and Igsf8. The authors confirmed and replicated the findings of Doi et al (26), that Alcam was expressed widely throughout the midbrain dopaminergic region.…”
Section: Cell Sorting For Parkinson's Disease Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…While approximately 370 antigens are targeted by monoclonal antibodies to cluster of differentiation (CD) molecules [8], this represents only a fraction of all molecules present on the cell surface (i.e., the surfaceome) and CD molecule screening has had limited success for nonhematopoietic stem cells [911]. Alternative approaches have been employed to evaluate the cell surface protein landscape based on transcriptomics [12], and physical and affinity enrichment strategies coupled with proteomics [13, 14], although each has limitations. Transcript abundance does not always correlate with protein abundance on the cell surface, transcriptomic data fail to inform subcellular localization, and the precise location of many membrane proteins are yet unannotated.…”
Section: Introductionmentioning
confidence: 99%